No benefit of surgery over physiotherapy for meniscal tears in adults with knee osteoarthritis - Kamper, Steven J.; Henschke, Nicholas (British journal of sports medicine, 2014)
This section features a recent randomised controlled trial that is indexed on PEDro, the Physiotherapy Evidence Database (http://www.pedro.org.au). PEDro is a free, web-based database of evidence relevant to physiotherapy. - - ▸ Surgery versus physical therapy for meniscal tear and osteoarthritis. New Engl J Med 2013;368:1675-84. - - Many people with osteoarthritis (OA) of the knee have damage to the meniscus,1 which is commonly treated by surgical excision of the damaged fragment; a procedure known as partial meniscectomy. However, it is not clear whether surgery of symptomatic meniscal tears improves pain and function in people with knee OA compared to conservative treatment. - - To assess whether adding arthroscopic meniscectomy to physiotherapy leads to greater improvements in pain and function than physiotherapy alone in older people with mild-to-moderate OA of the knee and a defined meniscus tear. - - Participants were recruited from tertiary referral centres in the USA. Patients over 45 years old with knee OA who reported symptoms consistent with a meniscus tear that had persisted for more than 1 month were eligible. Meniscus pathology and OA were confirmed by MRI. Clinical symptoms of a meniscus tear included at least one of the following: clicking, catching, popping, giving way, pain with pivot or torque, pain …
Gesehen am 01.09.2020